Pengaruh Struktur Modal, Likuiditas Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Sub Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia - Suci Imelda; Dian Ayu Andriani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine the Effect of Capital Structure, Liquidity, and Profitability on Stock Prices in Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange for the period 2022-2024. The analysis technique used multiple linear regression analysis. The results showed that DER, CR, and ROA simultaneously had no effect on stock prices with F count > F table (1.963 > 2.85) and a significance level of 0.136 > 0.05. DER partially has no effect on stock prices with t count 1.409 ˃ t table 2.024 and significant 0.167 > 0.05. CR partially has an effect and is significant on stock prices with a t count -2.147 < t table 2.024 and significant 0.038 < 0.05. ROA variables partially have no effect and are significant on stock prices with t count -0.148 ˃ t table 2.024 and significant 0.883 > 0.05. Based on the coefficient of determination, it shows the influence of the three independent variables on stock prices by 13.4% while the remaining 86.6% is influenced by other factors outside the study.